Peak and average rectified EMG measures: Which method of data reduction should be used for assessing core training exercises? - Hibbs, A. E.; Thompson, K. G.; French, D. N.; Hodgson, D.; Spears, R. (Journal of Electromyography and Kinesiology, 2011)
Core strengthening and stability exercises are fundamental for any conditioning training program. Although surface electromyography (sEMG) is used to quantify muscle activity there is a lack of research using this method to investigate the core musculature and core stability. Two types of data reduction are commonly used for sEMG; peak and average rectified EMG methods. Peak EMG has been infrequently reported in the literature with regard to the assessment of core training while even fewer studies have incorporated average rectified EMG data (ARV). The aim of the study was to establish the repeatability of peak and average rectified EMG data during core training exercises and their interrelationship. Ten male highly trained athletes (inter-subject repeatability group; age, 18 ± 1.2 years; height, 176.5 ± 3.2 cm; body mass, 71 ± 4.5 kg) and one female highly trained athlete (intra-subject repeatability group; age; 27 years old; height; 180 cm; weight; 53 kg) performed five maximal voluntary isometric contractions (MVIC) and five core exercises, chosen to represent a range of movement and muscle recruitment patterns. Peak EMG and ARV EMG were calculated for eight core muscles (rectus abdominis, RA; external oblique, EO; internal oblique, IO; multifidis, MF; latissimus dorsi, LD; longissimus, LG; gluteus maximus, GM; rectus femoris, RF) using sEMG. Average coefficient of variation (CV%) for peak EMG across all the exercises and muscles was 45%. This is in comparison to 35% for the ARV method, which was found to be a significant difference (P < 0.05), therefore implying that the ARV method is the more reliable measure for these types of exercise. Analysis of the inter-subject and intra-subject CV% values suggest that these exercises and muscles are sufficiently repeatable using sEMG. Five muscles were highly correlated (R > 0.70; RA, EO, MF, GM, LG) between peak and ARV EMG suggesting, that for these core muscles, the two methods provide a similar evaluation of muscle activity. However, for other muscles (IO, RF, LD) the relationship was found to range from poor to moderate (R = 0.10-0.70). The relationship between peak and ARV EMG was also affected by exercise type. Dynamic low and high-threshold exercises and asymmetrical low-threshold exercises had a moderate correlation between the variables (R = 0.74-0.81), while the static exercise showed a poor correlation (R = 0.46). It can be concluded that there are similarities between the two EMG variables, however due to the effect of type of exercise and muscle on the EMG data, both methods should be included in any future EMG study on the core musculature and core stability exercises.